BENTUK KEKERASAN VERBAL ANTARSISWA DI SEKOLAH MENENGAH PERTAMA DAN UPAYA PENCEGAHAN DARI GURU ILMU PENGETAHUAN SOSIAL (Studi Kasus SMP Negeri 3 Kaloran) - setiyaningrum, Raelesta; Lestari, Puji (Universitas Negeri Semarang, 2023)
Verbal violence is one form of violence that often occurs in the school environment. Students have the right to get protection from unpleasant actions that interfere with their learning process at school so efforts are needed to prevent verbal violence by the school. The purpose of this research: (1) to analyze the forms of verbal violence between students that occur at SMP Negeri 3 Kaloran; (2) to analyze efforts to prevent verbal violence between students by Social Science teachers. This research uses qualitative methods with a case study approach. Data collection techniques through interviews, observation, and documentation. Data validity techniques in this study use source triangulation and techniques with data analysis consisting of data reduction, data presentation and conclusions. The results showed that: (1) The forms of verbal violence that occurred between students at SMP Negeri 3 Kaloran were in the form of yelling, cursing, giving nicknames or labeling, degrading or harassing abilities, insulting, accusing, and threatening, ignore; (2) Efforts to prevent verbal violence at SMP Negeri Kaloran include efforts to cultivate good behavior habits, making persuasion advertisements providing positive criticism, guidance or coaching, providing information through socialization and counseling, and collaboration with other parties. Kekerasan verbal merupakan salah satu bentuk kekerasan yang kerap terjadi di lingkungan sekolah. Siswa berhak mendapatkan perlindungan dari tindakan tidak menyenangkan yang mengganggu proses belajarnya di sekolah sehingga diperlukan upaya pencegahan tindak kekerasan verbal oleh pihak sekolah. Tujuan dari penelitin ini ialah: (1) Menganalisis bentuk-bentuk kekerasan verbal antarsiswa yang terjadi di SMP Negeri 3 Kaloran; (2) Menganalisis upaya pencegahan tindak kekerasan verbal antarsiswa dari guru Ilmu Pengetahuan Sosial. Penelitian ini menggunakan pendekatan kulaitatif dengan desain studi kasus. Teknik pengumpulan data melalui wawancara, observasi, dan dokumentasi. Uji keabsahan data dalam penelitian ini menggunakan triangulasi sumber serta teknik analisis data terdiri dari reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa: (1) Bentuk kekerasan verbal yang terjadi antarsiswa di SMP Negeri 3 Kaloran ialah berupa membentak, memaki, memberi julukan atau melabel, merendahkan atau melecehkan kemampuan, menghina, menuduh, dan mengancam, mengabaikan.; (2) Upaya pencegahan tindak kekerasan verbal antarsiswa oleh guru IPS meliputi upaya penanaman kebiasaan berperilaku baik, pembuatan iklan persuasi, pemberian kritik yang positif, bimbingan atau pembinaan, pemberian informasi, kolaborasi dengan pihak lain.